Biomedical Simulation 4th International Symposium, ISBMS 2008, London, UK, July 7-8, 2008, Proceedings - Bello, Fernando; Edwards, Eddie (Theoretical Computer Science and General Issues,, 2008)
This book constitutes the refereed proceedings of the 4th International Symposium on Biomedical Simulation, ISBMS 2008, held in London, UK, in July 2008. The 19 revised full papers and 7 poster papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in four different sections corresponding to key areas and techniques of this constantly expanding field: finite element modeling, mass spring and statistical shape modeling, motion and fluid modeling and implementation issues. An additional section covers the posters presented at the meeting.